PROTOTYPE BABY INCUBATOR DENGAN SISTEM MONITORING BAK AIR BERBASIS INTERNET OF THINGS (IOT) - Muhammad Akbar Hariyono; Upik Ari Erlita; Bayu Setyo Wibowo (Health Media, 2023)
Baby Incubator is a rigid box-like enclosure for protection temperature range 32 – 37oC and humidity range 50 – 60% RH inside. Heating temperature occurs in Baby Incubator because heating element on, while humidity occurs when water evaporation in chamber which will make the air in a wet state. If water in chamber is empty or runs out, then it will affect the humidity in Incubator and it’s dangerous for babies, because it make back burnt effect from air in incubator to hot, then is necessary monitoring with concept of IoT who utilize the web of the internet for get hold of data temperature, humidity and water in chamber to make nurses easier for monitoring. Researchers use methods reseach and development that would create a product concept of a circuit prototype Baby Incubator IoT Based. The hardware on this prototype is made up of Arduino uno, NodeMCU ESP32S, Seven Segment, Sensor DHT22, Sensor ultrasonic US-100, Buzzer and push button. Based on the results of testing and validation from media experts and material experts, the Baby Incubator Prototype tool with Waterlevel Sensor equipped with IoT-Based Water Tank Monitoring, it can be concluded that the prototype can be declared to meet the category of eligibility Very Eligible to apply or proceed to the mass production stage so that it can facilitate in the process of monitoring temperature, humidity, and water volume in the Baby Incubator tool.